Computer-generated influencers: the rise of digital personalities - Mrad, Mona (2022)
Purpose The purpose of this study is to identify the key components pertaining and governing a Computer-Generated Influencer’s (CGI’s) identity and explores and analyzes the ensuing relationship between the CGI and its digital environment. Design/methodology/approach This study follows an exploratory approach using in-depth interviews of CGI followers. A total of 37 in-depth interviews were then analyzed using an inductive thematic approach to steer data coding. Findings CGIs are considered as brand entities that have a combination of components under their overall perceived identity. This study encompasses the different relational dimensions, whether from a follower’s followers, CGI-follower’s, CGI–human influencer’s or CGI-endorsed brand’s perspective. Originality/value This research contributes a seminal work in the field of virtual influencers.